1975
DOI: 10.1111/j.1432-1033.1975.tb04086.x
|View full text |Cite
|
Sign up to set email alerts
|

The Two Human Trypsinogens. Inhibiton Spectra of the Two Human Trypsins Derived from Their Purified Zymogens

Abstract: The two human anionic trypsinogens 1 and 2 were purified from human pancreatic juice by gel filtration on Sephadex G-100 and by chromatography on DEAE-cellulose. After activation of their respective zymogens by porcine enterokinase, human trypsins 1 and 2 were studied for their reaction with a wide variety of proteinase inhibitors. Kunitz pancreatic trypsin inhibitor and human pancreatic secretory trypsin inhibitor completely inhibited both human trypsins at a stoichiometric inhibitorto-enzyme ratio of one to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

1979
1979
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…The occurrence of two forms (anionic and cationic) of trypsinogen has been reported by a number of researchers (3, 14 -17). The cationic form of human trypsin, which represents the major part of trypsin activity of the whole pancreatic juice, is shown to be less inhibited by ovomucoid and soybean trypsin inhibitor than the anionic trypsin (18,19). Both human trypsins are completely inhibited by aprotinin or human PSTI, a physiological inhibitor co-localized with trypsins in the zymogen granules, at a stoichiometric enzyme-to-inhibitor ratio of one to one (18).…”
Section: Structure Of Mesotrypsin Cdna--mentioning
confidence: 94%
“…The occurrence of two forms (anionic and cationic) of trypsinogen has been reported by a number of researchers (3, 14 -17). The cationic form of human trypsin, which represents the major part of trypsin activity of the whole pancreatic juice, is shown to be less inhibited by ovomucoid and soybean trypsin inhibitor than the anionic trypsin (18,19). Both human trypsins are completely inhibited by aprotinin or human PSTI, a physiological inhibitor co-localized with trypsins in the zymogen granules, at a stoichiometric enzyme-to-inhibitor ratio of one to one (18).…”
Section: Structure Of Mesotrypsin Cdna--mentioning
confidence: 94%
“…From electrophoresis, we concluded that the pool of trypsinogen-rich fractions contained quantities of contaminating proteins of low molecular weight, requiring a new purification step. No explanation can be given for the presence of two trypsinogen bands: their slow kinetics of autoactivation indicated the absence of trypsin and suggested the existence of two forms of equine trypsinogens, conditions similar to those reported for human trypsinogen [4,10].…”
Section: Purification Of Equine Trypsinmentioning
confidence: 99%
“…The trypsinogen-rich fractions were identified by trypsin activity measurement (BAPNA substrate) on a 100 µL aliquot volume of each fraction (after trypsinogen activation by 1% enterokinase) pooled, dialysed and concentrated. Trypsinogen in the protein pool was then activated by 1% porcine enterokinase (0.01 M Tris-HCl buffer, pH 7.8, 20 mM CaCl 2 , 0.05 M NaCl; +4°C, 6 h) [10]. The last step was affinity chromatography on 4B Sepharose linked to aprotinin [30].…”
Section: Chromatographic Steps and Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Human trypsin is known to exist in two forms, a cationic species, which is the major component of human pancreatic juice, and an anionic species, which comprises about 10 to 20% of the total trypsin activity (Figarella et al 1975). While the latter is fully inactivated by the soya-bean inhibitor, the predominant cationic species is only weakly inhibited (Figarella et al 1974).…”
Section: Symposium Proceedings '979mentioning
confidence: 99%